2017
DOI: 10.1017/s0033291717003002
|View full text |Cite
|
Sign up to set email alerts
|

Duration of untreated psychosis and neurocognitive functioning in first-episode psychosis: a systematic review and meta-analysis

Abstract: There may not be a generalised association between DUP and neurocognition, however, specific cognitive functions may be associated with longer DUP or delayed help-seeking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 92 publications
5
23
1
1
Order By: Relevance
“…Moreover, we dichotomized DUP into short (<12 months) and long (>12 months) based on a number of studies that used this cutoff to define long and short DUP (refs. 4,[38][39][40][41] ), including those predicting treatment outcomes in early psychosis 42 and poorer outcomes after the first hospitalization 43 .…”
Section: Duration Of Untreated Psychosismentioning
confidence: 99%
“…Moreover, we dichotomized DUP into short (<12 months) and long (>12 months) based on a number of studies that used this cutoff to define long and short DUP (refs. 4,[38][39][40][41] ), including those predicting treatment outcomes in early psychosis 42 and poorer outcomes after the first hospitalization 43 .…”
Section: Duration Of Untreated Psychosismentioning
confidence: 99%
“…Many mental health services devote significant resources to early intervention in psychosis based, at least partly, on the premise that reducing DUP improves outcomes [10][11][12][13][14][15] . This notion has been investigated in over a hundred studies examining a number of different outcomes, summarized in several meta-analyses [16][17][18][19][20][21][22][23] . However, due to the inclusion of overlapping samples in different meta-analyses, and differences in inclusion criteria, definition of outcomes, reporting standards and analysis techniques, it is difficult to generate a clear hierarchy of evidence.…”
mentioning
confidence: 99%
“…They were also younger and had a longer DUP. While longer DUP is associated with poorer outcomes in general (Marshall et al ., 2005; Perkins et al ., 2005), a recent meta-analysis found that the relationship between DUP and most cognitive domains is not significant, particularly for studies with DUP longer than 1 year (Allott et al ., 2017), as was the case for this study.…”
Section: Discussionmentioning
confidence: 52%